The effectiveness of clavipectoral fascia plane block for analgesia after clavicle surgery: A report of five cases - Atalay, Yunus Oktay; Çiftçi, Bahadır; Ekinci, Mürsel; Yesiltaş, Serdar (Edizioni Minerva Medica, 2020)
Clavicle fracture is common in men and children after adirect fall on shoulder during sport activity such as cycling or an injury during a traffic accident.1 The pain afterclavicle fracture surgery may be managed with combinedsuperficial cervical plexus-interscalene block and recently clavipectoral fascia plane block (CPB).1-3 In the literature, data about CPB is so limited (just three case reports),however it seems a good alternative to brachial plexusblock for pain management after clavicle fracture.3-5 Inthis case series we wanted to report the effectiveness ofCPB being performed in five patients underwent claviclefracture surgery. This study was approved by the IstanbulMedipol University Ethics and Research Committee.
Keywords: Clavipectoral Fascia; Clavicle Surgery; Plane Block; Analgesia